Use of a type IIB external skeletal fixator in experimental tarsocrural arthrodesis in dogs - Dórea Neto, Francisco de Assis; Oriá, Arianne Pontes; Padilha Filho, João Guilherme [UNESP]; Regonato, Everton; Moreno, Juan Carlos Duque; Canola, Júlio Carlos [UNESP] (My University, 2012)
The aim of the present study was to evaluate the usefulness of type IIb external skeletal fixators with a transarticular pin in experimental tarsocrural arthrodesis. Twelve adult mongrel dogs of both sexes, ranging in age from two to five years and weighing 12 to 25kg, were used. The configuration of the fixator consisted in the application of a transarticular Steinmann pin and of centrally threaded pins to the proximal portion of the tibia and calcaneus and to the distal portion of the metatarsal bones. In addition, Schanz pins were inserted into the medial and lateral side of the tibia and into the medial side of the metatarsal bones. Radiographs were taken 15; 30 and 45 days after surgery. Bone fusion of the treated joints were observed at 30 days in all animals, and the implants were removed after 45 days. Loosening of the centrally threaded pins was observed in all groups, especially for those applied to the calcaneus. The configuration of the external fixator proposed here was found to be satisfactory in terms of bone union for all joints during the same period, irrespective of the weight of the animal.
Keywords: Dog; Experimental surgery; Joint fusion; Small animals; Veterinary orthopedics; Animalia; Canis familiaris